The Development of Small and Medium-sized Businesses and its Impact on the Trend of Unemployment in Kazakhstan - Toty Bekzhanova; Murat Aliyev; Gulmira Tussibayeva; Miyatbek Altynbekov; Aigul Akhmetova (Australasian Accounting, Business and Finance Journal, 2023)
This study is focused on conducting research on the development of entrepreneurship in small and medium-sized businesses, which is one of the key priorities in the Republic of Kazakhstan since the development of small and medium-sized businesses allows solving the issue of reducing unemployment in the country, as well as the outflow of youth. The development of small and medium-sized businesses allows the creation of new jobs where the population of Kazakhstan can offer their candidacy for vacant places. The information base of the study includes the works of Russian, European, and American specialists involved in the study of the development of small and medium-sized businesses, as well as those dealing with unemployment and how it can be reduced through the development of small and medium-sized businesses. The results of this study allowed forming a number of recommendations aimed at the development of small and medium-sized businesses, as well as increasing the level of employment among the population of the Republic of Kazakhstan.
Keywords: Business; SMEs; Entrepreneurship; Labour market; Business support measures; Kazakhstan.